The quest for a 21st century Islamic economics curriculum for universities in the Muslim world: the case of IIUM - Haneef, Mohamed Aslam; Abdullah Yusof, Selamah; Mohd Amin, Ruzita (2011)
Development has been, and is, a central concern for many countries for the most part ofthe 20th Century. Over the decades, development has taken a much wider and holistic approach. In 1999 the World Bank introduced the Comprehensive Development Framework (CDF) which stated that development should be viewed as a multi-dimensional process that covered social, structural, human, governance, environmental, economic and financial spheres. This paper focuses on the role of education, more specifically on higher education, in producing manpower who are not only skillful but at the same time infused with the desired ethics and values needed to achieve comprehensive development. It discusses the objectives of education and provides an overview of the literature on curriculum development. The discussion also looks at the Islamic perspective of education since the more holistic, comprehensive approach to development is congruent with the Islamic viewpoint on development. The paper then presents a model of an integrated curriculum structure that fulfils the Islamic objectives of higher education while ensuring the various needs of the market are met. The paper concludes with a discussion on the challenges that might be faced in implementing the proposed curriculum and provides some recommendations in improving existing curriculums to meet the objectives of comprehensive development.